The Construction of Plausible Futures in Dystopian Literature: A Theoretical Approach from Social and Cultural Semiotics (Anclajes, 2023)
Dystopian fiction is a discursive genre made up of cultural products (literary texts, movies, series) aimed at producing a particular type of effects of sense in the model reader: ideally, in consuming them, readers will be capable of conducting a critical evaluation of their socio-political circumstances. Thus, dystopian fiction – which is a fictional discourse – aims at being the source of socio-political change through the intervention in the discursive sphere of the non-fictional. This article approaches the genre of dystopian fiction in literature from a semiotic perspective. Specifically, it focuses on studying the type of imagination and construction of possible worlds that define it. The thesis it presents is that dystopian fiction is characterised by a construction of futures that are plausible, that is, that have an anchorage in reality as it is and are therefore viable,unlike what happens in science fiction.
Keywords: Literature; Dystopia; Semiotics; Possible worlds; Literary genres